1987
DOI: 10.1055/s-2007-1017107
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effect of Acetylsalicylic Acid (ASA) Versus a Lithium-ASA combination: An Evoked Potential Study Employing Radiant Heat Stimulation with a CO2Laser

Abstract: Objective experimental algesimetry was used to assess quantitative differences in analgesic properties between acetylsalicylic acid (ASA, 750 mg) and a special combination of ASA, trilithium citrate and quinine-2 HCl (750 mg, 126 mg, 4.5 mg) in a placebo-controlled double-blind crossover study on nine healthy subjects. Radiant heat stimulation was applied with a CO2 laser and somatosensory evoked vertex potentials (LSEP) were recorded while the subjects were simultaneously engaged in an adaptive pursuit tracki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…Kobal et al (1990) found only significant modulation of the evoked potentials and not subjective pain ratings after nasal gaseous CO 2 stimulation. Supporting this Schaffler et al (1987) found good effect of acetylsalicylic acid on the evoked vertex potential from radiant heat stimulation.…”
Section: Analgesic Assessment By Experimental Human Pain Modelssupporting
confidence: 54%
See 1 more Smart Citation
“…Kobal et al (1990) found only significant modulation of the evoked potentials and not subjective pain ratings after nasal gaseous CO 2 stimulation. Supporting this Schaffler et al (1987) found good effect of acetylsalicylic acid on the evoked vertex potential from radiant heat stimulation.…”
Section: Analgesic Assessment By Experimental Human Pain Modelssupporting
confidence: 54%
“…Skin, nasal, and dental mucosa. Acetylsalicylic acid has been tested against pain from radiant heat, electrical stimulation, nasal gaseous CO 2 stimulation, and infusion of low pH solutions (Cruccu et al, 1982;Schaffler et al, 1987;Steen et al, 1996). Kobal et al (1990) found only significant modulation of the evoked potentials and not subjective pain ratings after nasal gaseous CO 2 stimulation.…”
Section: Analgesic Assessment By Experimental Human Pain Modelsmentioning
confidence: 99%
“…Acute models Skin/nasal and dental mucosa: Acetylsalicylic acid has been tested against pain from radiant heat, electrical stimulation, nasal gaseous CO2 stimulation and infusion of low-pH solutions [8][9][10]. Pain from repeated mechanical impact of the interdigital web is a classical model for detecting analgesia from nonsteroidal antiinflammatory drugs (NSAIDs), and this model is also sensitive to analgesia from acetylsalicylic acid [11].…”
Section: Acetylsalicylic Acid (Aspirin)mentioning
confidence: 99%
“…Topical ibuprofen seemed to have some advantages over systemic ibuprofen for attenuation of exercise-induced jaw-muscle pain, indicating that a peripheral pain mechanism is important in this model [31]. Experimental models involving NSAIDs shows how a peripheral mediated analgesia can be detected by central measures, because the sum of incoming nociceptive activity to the central nervous system (CNS) is reduced [9]. Generally, it could be seen that evoked brain potentials from electrical skin stimulation were more sensitive than the subjective pain rating [13,20,38].…”
Section: Mechanistic Aspectsmentioning
confidence: 99%
“…It appears that the wide gap between preliminary experimental data obtained in animals and human pain should be bridged by quantitative measurement of drug effects in human volunteers in order to predict the possible clinical suitability of any compounds. Many attempts for measuring pain and analgesic effects in volunteers using event-related potentials [3] have been reported (reviewed by Chudler and Dong [4] and Stowell [5]; [6][7][8][9][10][11][12]). Many of these studies suffer either from limited reproducibility due to changes in the tissue irritated by the noxious stimulus, or from the lack of adequate control measurements which take into account vigilance, adaptation, and learning effects.…”
Section: Introductionmentioning
confidence: 99%